2017
DOI: 10.5376/ija.2017.07.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Basil Leaf (<i>Ocimum gratissimum</i>) as Dietary Additives on Growth Performance and Production Economics of <i>Clarias gariepinus</i>

Abstract: Synthetic antibiotics have been widely used in fish culture systems as performance enhancers and controlling stress.These antibiotics are expensive and induce microbial resistance with consequent environmental effects. Phytogenic plants have potential as alternative antibiotics, but there is little information on their utilization in fish nutrition. Therefore the evaluation of Basil (Ocimum gratissimum) leaf meal on the growth response, nutrient utilization and production economics of Clarias gariepinus. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…Iheanacho et al [1] reported significant increases in weight gain, specific growth rate and final weight when C. gariepinus juvenile were exposed to varying concentrations (0.25, 0.50, 0.75 and 1.0 g/35 L) of ginger as compared to the control. The same trend was observed by Adewole [45] who also reported significant increases in growth parameters (final weight, weight gain, specific rate and relative growth rate) in C. gariepinus fed roselle supplemented diets when compared with the control. Therefore, the positive response to growth in treated fish, especially those receiving 1% inclusion level of ginger, could be attributed to the average proximate content of ginger which is a good source of mineral elements, vitamins and contains good number of phytochemical constituent that enhance growth and health of animals through actions as the stimulation of the secretion of pancreatic enzymes and the bile from the liver that induce fast feed digestion and helps to balance the intestinal bacteria [46].…”
Section: Discussionsupporting
confidence: 85%
“…Iheanacho et al [1] reported significant increases in weight gain, specific growth rate and final weight when C. gariepinus juvenile were exposed to varying concentrations (0.25, 0.50, 0.75 and 1.0 g/35 L) of ginger as compared to the control. The same trend was observed by Adewole [45] who also reported significant increases in growth parameters (final weight, weight gain, specific rate and relative growth rate) in C. gariepinus fed roselle supplemented diets when compared with the control. Therefore, the positive response to growth in treated fish, especially those receiving 1% inclusion level of ginger, could be attributed to the average proximate content of ginger which is a good source of mineral elements, vitamins and contains good number of phytochemical constituent that enhance growth and health of animals through actions as the stimulation of the secretion of pancreatic enzymes and the bile from the liver that induce fast feed digestion and helps to balance the intestinal bacteria [46].…”
Section: Discussionsupporting
confidence: 85%
“…The inclusion of basil leaves in this study improved the SGR, and a similar result was recorded by El-Dakar et al (2008) following the inclusion of 2% dried basil leaves in the diet of hybrid tilapia fry (Oreochromis niloticus x Oreochromis aureus). This result is in line with the work of Adewole et al (2017), who showed that the use of O. gratissimum leaves as an additive in the diet of Clarias gariepinus improved to a certain level the SGR compare to control. Oluyemi and Funmi (2015) also reported that the addition of 40 mg/g of O. gratissimum leaves in the diet of Clarias gariepinus improved the SGR.…”
Section: Discussionsupporting
confidence: 91%
“…The progressive response in the growth of treated fish especially at 0.8% was associated with the presence of roselle which Pietta (2000), Mahadevan and Pradeep (2009) ) reported that the plant contain minerals, vitamins, flavonoids, gossypetine, sabdaretine and virtuous number of phytochemical components that boosts the growth and health status of animals. Feed utilization values also followed similar pattern with the growth parameters with the highest feed intake from RM3 diet which was in agreement with findings of Adewole (2014) who reported that roselle fed to Clarias gariepinus gave the highest feed utilization indices.…”
Section: Discussionsupporting
confidence: 91%